Chitosan-based electrospun membranes: Effects of solution viscosity, coagulant and crosslinker. (1st May 2020) - Dodero, Andrea; Brunengo, Elisabetta; Alloisio, Marina; Sionkowska, Alina; Vicini, Silvia; Castellano, Maila
Graphical abstract: Highlights: Chitosan electrospun membranes were obtained using a low amount of acetic acid. The effect of polymer concentration on fibre morphology was established. The best coagulation medium for chitosan was found to have a slightly basic pH. Chitosan was successfully crosslinked via phosphate ions. The obtained membranes represent a promising class of biomedical products. Abstract: Chitosan-based membranes were prepared via electrospinning technique using a low concentrated acetic acid solution as solvent and poly(ethylene oxide) as co-spinning agent. Different solutions were rheologically characterized and increasing the solution viscosity was found to correspond to a better-defined morphology. The membranes were first subjected to a coagulation process with different baths in order to stabilize chitosan and the mats were found not able to withstand a strongly basic environment. Subsequently, a physical and a chemical crosslinking approach were separately optimized to obtain stable mats whose composition was assessed via thermogravimetric and spectroscopic techniques, proving in both cases the elimination of the co-spinning agent. Above all, the ionically crosslinked mats represent a class of extremely promising biomedical products being probably highly biocompatible and characterized by thin and homogenous nanofibers with a diameter of 200 nm, thus showing the ideal structure to foster cell viability.